Ngā Kare-ā-Roto: Māori Cultural Understandings and Emotional Expression - Leonie Pihama; Jenny Lee-Morgan; Rangi Matamua; Hineitimoana Greensill; Papahuia Dickson (Genealogy, 2025)
This article ‘Ngā Kare-ā-roto: The Ripples Within’ provides an overview of findings related to Māori views, understanding and expressions of emotions through a Māori cultural lens. One of the key findings from the research project ‘Ngā Kare-ā-roto’ highlighted that emotions are expressed through a range of cultural practices that have served to bring collective understandings to support emotional wellbeing for Māori. At the centre of this research is the revitalisation of ancestral knowledge and practices to support emotional expression. The social and cultural significance of this project is highlighted by Indigenous researchers who have noted the direct relationship of emotions such as grief and trauma to wellbeing. This article provides an outline of kaikōrero (speakers/participants) views on the place of whakataukī (proverbial sayings) in the expression of emotions and emotional states of being. We begin with an overview of the significance of this work to supporting wellbeing and healing. We then move to providing a range of examples that were shared throughout the project that give insights into the ways in which emotions for Māori are framed within our ancestral and cultural understandings, in particular in regards to collective expressions of tikanga (cultural practices) and whakataukī that have been handed down through te reo Māori (Māori language) as sources of knowledge, guidance and learning.